Тактика лечения радикулярной кисты, расположенной в области зуба, имеющего сложное анатомическое строение (зуб в зубе) (LLC "Endo Press", 2020)
Radicular cyst treatment mostly requires surgical approach. But there are cases where this method is not effective for example when the radicular cyst is present at the apex of the anatomically difficult configuration of the «dens in dente» tooth. Ingrowths of the tooth structures (Dens Invaginatus) or the anatomical type of the «tooth inside the tooth» («dens in dente») is the tooth organ development disorder and rarely met on the daily basis. Teeth with such anatomical structure have parts of dentin and enamel that grow into the pulp chamber and sometimes into the apical part of the tooth. The main problem in treating this pathology is the lack of the information about. Atypical anatomical variety of root canal configuration creates difficulties for a quality endodontic treatment. Quality of the surgical treatment mostly depends on the quality of the endodontic treatment. In order to solve the problem in treating this pathology, new approach of treatment and diagnostics were developed. The diagnostics was carried out using digital radiography and cone beam computer tomography. Treatment consisted of two parts: conventional (using dental operating microscope) and surgical with apical tip resection and retrograde preparation and obturation.